MANAGING AI-DRIVEN DIGITAL TRANSFORMATION IN VOCATIONAL EDUCATION: A JURIDICAL PERSPECTIVE ON ACADEMIC DIGITALIZATION - Supriyatno Supriyatno; Marsinah Marsinah; Fitria Marisya; M Bambang Purwanto (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2026)
The rapid advancement of digital technology has driven higher education institutions, particularly vocational education, to adopt Artificial Intelligence (AI) in academic management and learning systems. While AI offers efficiency and data-driven decision-making, its implementation raises managerial and legal challenges, especially regarding data protection and accountability. This study employed a descriptive qualitative approach using library research. Data were collected from reputable international journals, academic books, policy reports, and Indonesian legal documents related to education management, AI, and digital governance. The analysis was conducted using descriptive-analytical techniques, synthesizing managerial, technological, and legal perspectives. The findings indicate that AI-based digital transformation enhances the effectiveness of vocational education management, including learning personalization, academic evaluation, and administrative services. However, the use of AI also introduces potential risks such as algorithmic bias, over-reliance on digital systems, and vulnerability of students’ personal data. From a legal perspective, the implementation of AI in vocational education must be aligned with Indonesian regulations, particularly the Personal Data Protection Act and the Electronic Information and Transactions Act. The study concludes that successful digital transformation in vocational education requires an integrated framework that combines adaptive management, responsible AI use, and robust legal compliance to protect students’ rights and ensure sustainable educational governance.